Molecular interaction and mechanism of cellulose as thickening and reinforcement agent in carrageenan biocomposite for hard capsule - Nur Amalina, Ramli (2023)
Plant-based hard capsule has a high market demand due to its versatility as a drug delivery carrier for vegetarians. The production volume of plant-based hard capsules is limited and still growing for a broader over-the-counter market. Carrageenan is a cost-effective and promising material to be developed as a hard capsule. However, it was demonstrated to have low mechanical strength, which limits its potential application. Fillers of hydroxypropyl methylcellulose (HPMC), carboxymethyl sago starch (CMSS) and cellulose nanocrystals (CNC) were employed in the carrageenan matrix as thickening and reinforcement agents. It is hypothesized to increase the biocomposite properties by the formation of intermolecular interaction. This work aims to characterize and evaluate the mechanical and thermal properties of carrageenan biocomposite incorporated with HPMC and CMSS at different concentrations; to recognize the molecular interaction between carrageenan, HPMC and CMSS via 1H NMR and quantum mechanics simulation using Gaussian 09W software; to investigate the formation of CNC in deep eutectic solvent (CNCDES) as reinforcement agent at different ultrasonication intensity and feed concentration and evaluate the properties of the reinforced carrageenan biocomposite; and to elucidate the hydrogen bonding mechanism behind the formation of DES and the molecular interaction with CNC as the reinforcement agent in carrageenan biocomposite and hard capsules. Carrageenan biocomposite with the incorporation of 0.8 w/v% HPMC presented significant effects on the tensile and capsule loop strength with an improvement of 59.1 and 46.9%, respectively. The glass transition of the Carra-HPMC film increased from 37.8 to 65.3 C, implying higher thermal stability. These improvements could be elucidated by the hydrogen bond formation between sulphate (carrageenan) – hydroxyl (HPMC) groups at a distance of 1.36 Å, as simulated in quantum mechanics software. This is in agreement with the downfield movement around 3.20 ppm of the carrageenan proton to 3.33 ppm in the 1H NMR spectrum, which suggests the intermolecular interaction between carrageenan and HPMC. The incorporation of CMSS, however, increased the moisture content of the biocomposite. CNC was prepared in DES, which improved its dispersibility and stability in the solution state. The zeta potential of CNC was −48.1 mV, which was sufficient to avoid particle agglomeration. The high crystallinity of CNCDES resulted in a significant improvement in the film tensile and the capsule loop strength to 84.7 MPa and 43.7 N, respectively. The intermolecular hydrogen bond was formed between hydroxyl group (CNC) – chloride ion (DES) at a bond length of 2.47 Å. The bond formation between CNC and DES modified the molecular structure of CNC becoming looser, which could explain the swelling mechanism of CNC when dispersed in DES. The topography of the biocomposite film with CNC prepared in DES presented a smoother surface with an average roughness of 19.4 nm, compared to the film with CNC in deionized water. Carra-HPMC/CNCDES hard capsule also presented a good performance on disintegration and drug dissolution following the regulation of US Pharmacopoeia. These aforementioned results indicate that HPMC and CNC would be ingenious thickening and reinforcement agents in producing carrageenan hard capsules.